Gaze Behavior in a Natural Environment with a Task-Relevant Distractor: How the Presence of a Goalkeeper Distracts the Penalty Taker - Kurz, Johannes; Hegele, Mathias; Munzert, Jörn (Frontiers in Psychology, 2018)
Gaze behavior in natural scenes has been shown to be influenced not only by top-down factors such as task demands and action goals but also by bottom-up factors such as stimulus salience and scene context. Whereas gaze behavior in the context of static pictures emphasizes spatial accuracy, gazing in natural scenes seems to rely more on where to direct the gaze involving both anticipative components and an evaluation of ongoing actions. Not much is known about gaze behavior in far-aiming tasks in which multiple task-relevant targets and distractors compete for the allocation of visual attention via gaze. In the present study, we examined gaze behavior in the far-aiming task of taking a soccer penalty. This task contains a proximal target, the ball; a distal target, an empty location within the goal; and a salient distractor, the goalkeeper. Our aim was to investigate where participants direct their gaze in a natural environment with multiple potential fixation targets that differ in task relevance and salience. Results showed that the early phase of the run-up seems to be driven by both the salience of the stimulus setting and the need to perform a spatial calibration of the environment. The late run-up, in contrast, seems to be controlled by attentional demands of the task with penalty takers having habitualized a visual routine that is not disrupted by external influences (e.g., the goalkeeper). In addition, when trying to shoot a ball as accurately as possible, penalty takers directed their gaze toward the ball in order to achieve optimal foot–ball contact. These results indicate that whether gaze is driven by salience of the stimulus setting or by attentional demands depends on the phase of the actual task.